Análise das tensões entre religião e cultura no acervo de arte popular do Instituto do Patrimônio Histórico e Artístico Nacional (IPHAN – AL) - Costa, América de Oliveira (2021)
Based on the collection of the popular art collection at the Iphan Museum, a collection based on the private collection of Tania de Maya Pedrosa, we will work on concepts of cultural heritage and its relationship with religion, relating the ideas of religion and culture. The development of this proposal resulted in three chapters, and in the first chapter we will deal with the theoretical aspects of religion and how it was encompassed by culture; in the second, we will analyze in loco the popular art collection Invenção da Terra – Tania collection by Maya Pedrosa, observing the elements of mixed religion with the cultural, which we will call here the cultural religion of the collection; and in the third, we will deal with the analysis of the life and work of Dona Irinéia, popular artist from the Quilombo de Muquém, relating the concepts of the first and second chapters. This will be done with bibliographical research, iconographic analysis and in-depth interviews